The Effect of Sowing Norms on Number of Plant Bushes of Prospective “Kizilkurgon” Variety of Barley - Khudaykulov Jonibek Bozarovich; Buriev Iskandar Astanovich (Zien Journals, 2022)
This article presents data on the effect of sowing norm on the winter frost resistance of barley varieties and the number of stalks. Barley cultivars were observed to have a high level of winter frost resistance. So, based on the analysis of the obtained data, in our scientific research conducted in the soil and climate conditions of the Tashkent region, it was observed that the amount of plants in barley varieties died in an average amount of 8.5-11.7%. When the thickness of seedlings at the end of vegetation is determined, the control is 265-351-412 m2 / unit according to sowing norm in the "Ixtiyor" variety, and 284-368-437 m2 /unit in the "Kizilkurgon" variety it was noted that the seedlings were preserved.
Keywords: Wheat; experiment; design; replication